Shape optimization and uncertainty assessment of a centrifugal pump. Issue 2 (1st February 2022) - Fracassi, Alessia; De Donno, Remo; Ghidoni, Antonio; Congedo, Pietro Marco
ABSTRACT: Centrifugal pumps, being used nowadays for many applications, must be suited for a wide range of pressure ratios and flow rates. To overcome difficulties arising from the design and performance prediction of this class of turbomachinery, many researchers have proposed coupling Computation Fluid Dynamics (CFD) codes and optimization algorithms for fast and effective design procedures. However, uncertainties are present in most engineering applications such as turbomachines, and their influence on performance should be assessed. In this work, some advanced optimization techniques are applied to the blade optimization of a European Research Community on Flow, Turbulence and Combustion (ERCOFTAC)-like pump, and the robustness of the optimal profiles through an uncertainty quantification study is assessed. Two primary sources of uncertainty are considered: (i) equipment uncertainties, primarily the rotational speed of the pump shaft that also affects the flow rate; and (ii) uncertainties in the inlet turbulence quantities in CFD simulations.